PENGOLAHAN LIMBAH MENJADI PUPUK KOMPOS BAGI SISWA SEKOLAH DASAR NEGERI 37 SUNGAI BANGEK KOTA PADANG UNTUK MEWUJUDKAN GREEN ECONOMY - Ayunis, Ayunis; Muhelni, Leila; Rahman, Adipo (Jurnal Hilirisasi IPTEKS, 2024)
Activities at school produce organic waste such as food waste from the canteen and student snacks as well as leaves from trees around the school. This organic waste is often not handled properly, causing environmental problems such as unpleasant odors, the spread of disease, and pollution of the environment around schools. With this problem, waste processing activities are carried out. this processing activity aims to provide guidance to students at State Elementary School 37 Sungai Bangek, Balai Gadang Village, Koto Tangah District, in utilizing waste as an effort to realize the concept green economy. This activity is also expected to increase students' awareness of the importance of environmentally friendly waste management and foster positive habits in protecting the environment from an early age. This program involves 28 students with a participatory approach through a series of educational and practical activities, such as sorting organic waste, making compost from organic waste and also increasing awareness of the importance of waste management and implementing sustainable economic principles from an early age. Activity methods include (1) socialization; (2) training and application of technology. The results of this activity show an increase in students' knowledge and skills in utilizing waste into products of economic value. Apart from that, this program also has an impact on changing student behavior in managing waste in the school and home environment. It is concluded that this activity can gain knowledge and skills in processing organic waste into valuable and useful ones. This activity is also able to have a positive impact, especially on elementary school students, because they care about the environment and become a model for other schools in integrating environmental education and education. green economy in the Dasa education curriculum.